Potency of Carica papaya Leaf Extract as Thrombocytopenia Therapy for Dengue Hemorrhagic Fever: A Systematic Review of Randomized Control Trials - Firmansyah Sabir, Muhammad Farid; Suciangto, William; Rahmani, Muhammad Zaki; Eka Lestari, Anfauziyah; Mubin, Risna Halim (SCRIPTA SCORE Scientific Medical Journal, 2023)
Background: Dengue fever is a common disease in tropical countries. According to the data from the Indonesia Ministry of Health, there were 71.633 Dengue Haemorrhagic Fever (DHF) cases reported in Indonesia, with approximately 459 people dying from the disease. Thrombocytopenia is the most common clinical feature of DHF and often causes serious complications if not treatedproperly. Several studies have analyzed the potency of Carica papaya leaf which has been proven asan effective therapy for thrombocytopenia. Objectives: This systematic review aims to discover the potency of Carica papaya leaf extract as a therapy for thrombocytopenia. Method: Literature was searched by using keywords in accordance with the topic, then filtered according to the inclusion criteria that had been determined according to the PRISMA rules. Publication bias in this reviewwas conducted subjectively using the Revman 5.4 software. Results: From 138 studies, it wasfound that screening was carried out based on inclusion criteria, including a randomized controlled trial study in humans with a population of dengue fever patients and received the intervention of papaya leaf extract so that 6 studies were included in the inclusion study, which was then carried out by qualitative synthesis from the study. Based on the results of the qualitative analysis, it wasfound that there was a faster and more significant improvement in the platelet count between the intervention group compared to the control group in the 6 studies. Conclusion: Carica papaya leaf extract has potential as a thrombocytopenia therapy in dengue fever patients.